If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + 5)(3x + -8) = 0 Reorder the terms: (5 + 7x)(3x + -8) = 0 Reorder the terms: (5 + 7x)(-8 + 3x) = 0 Multiply (5 + 7x) * (-8 + 3x) (5(-8 + 3x) + 7x * (-8 + 3x)) = 0 ((-8 * 5 + 3x * 5) + 7x * (-8 + 3x)) = 0 ((-40 + 15x) + 7x * (-8 + 3x)) = 0 (-40 + 15x + (-8 * 7x + 3x * 7x)) = 0 (-40 + 15x + (-56x + 21x2)) = 0 Combine like terms: 15x + -56x = -41x (-40 + -41x + 21x2) = 0 Solving -40 + -41x + 21x2 = 0 Solving for variable 'x'. Factor a trinomial. (-5 + -7x)(8 + -3x) = 0Subproblem 1
Set the factor '(-5 + -7x)' equal to zero and attempt to solve: Simplifying -5 + -7x = 0 Solving -5 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -7x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -7x = 0 + 5 -7x = 0 + 5 Combine like terms: 0 + 5 = 5 -7x = 5 Divide each side by '-7'. x = -0.7142857143 Simplifying x = -0.7142857143Subproblem 2
Set the factor '(8 + -3x)' equal to zero and attempt to solve: Simplifying 8 + -3x = 0 Solving 8 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -3x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -3x = 0 + -8 -3x = 0 + -8 Combine like terms: 0 + -8 = -8 -3x = -8 Divide each side by '-3'. x = 2.666666667 Simplifying x = 2.666666667Solution
x = {-0.7142857143, 2.666666667}
| x+[x+1]=1.10 | | y=-5+2(-2) | | a^2+10ab+25b^2-49=0 | | (x+49)(x+4)=O | | x^2-5x+6.25-14=6.25 | | 1x-2y=10 | | w+9=-7 | | 5-4x=x-1.5 | | 5x-0.8=0.2+3x | | 6y-1y-12= | | =6z-(3z-6)+(7-8z) | | 15=3x-6x-3 | | 6y^2+8y-9y-12= | | X+x+1+x+2=274 | | -36=p-6 | | 3=18x+6x^2 | | G(x)=8sin(5x^6) | | 6y^2+8y-8y-12= | | k^2+12k=-35 | | 2x^3-2x^2+7x-40=0 | | 9d+d-d+2-3d=0 | | 6y^2+8y-12= | | (49x^2)-(25)=0 | | 3(x+y)-2(2y+x)+y= | | 1+n/3=-6 | | 2x+8+2x=10+2x+12 | | 1.2+y=-8 | | 4x-5=6x-13 | | 5-(x+3)+3x+3(x+2)= | | -18+12-3= | | (9x+9)+(-12x+24)= | | 4(x+3)+(x+6)+2(x-3)= |